Impact of Social Media on Customer Engagement and Brand Perception: A Case of Kathmandu Valley - Adhikari, Anudita (Nepalese Journal of Business, 2025)
This study examines the impact of social media on customer engagement and brand perception: A case of Kathmandu Valley. Customer engagement and brand perception are the dependent variables. The selected independent variables are content strategy, customer targeting, interactivity, community building, and influencer partnership. The primary source of data is used to assess the opinions of respondents regarding content strategy, customer targeting, interactivity, community building, influencer partnership, customer engagement, and brand perception. The study is based on primary data. The primary data were gathered from 146 respondents through questionnaires. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of social media on customer engagement and brand perception: A case of Kathmandu Valley. The study showed a positive impact of content strategy on customer engagement and brand perception. It indicates that getting the right content, to the right people, in the right place, at the right time leads to increase in customer engagement and brand perception. Similarly, the study showed a positive impact of customer targeting on customer engagement and brand perception. It indicates that higher the customer targeting, higher would be the customer engagement and brand perception. Likewise, the study also revealed a positive impact of interactivity on customer engagement and brand perception. It indicates that communication between people and digital devices leads to increase in customer engagement and brand perception. Further, the study observed a positive impact of community building on customer engagement and brand perception. It indicates that bringing people together and creating a sense of belonging leads to increase in customer engagement and brand perception. In addition, the study observed a positive impact of influencer partnership on customer engagement and brand perception. It indicates that collaboration between a brand and an individual who has a significant following on social media platforms leads to increase in customer engagement and brand perception.